The Songbirds Bible: A Visual Directory of 100 of the Most Popular Songbirds in North America - Proctor, Noble S. (Ronnie Sellers, 2006)
Keywords: Identification; Identification; Birdsongs; North America; Songbirds; dept.bio; faculty_collection

Habitat, food habits, and productivity of Northern Goshawks nesting in Connecticut - Becker, T.E.; Smith, D.G.; Bosakowski, T. (Studies in Avian Biology, 2006)
We documented active nests of the Northern Goshawk (Accipiter gentilis) at 16 different areas in Connecticut from 1997-1999. A total of 176 prey individuals were identified from remains found under goshawk nests and prey-plucking posts. Birds represented the dominant component of diets (70.5%) with a lower contribution from mammals (29.5%). Overall, Connecticut goshawk diets were dominated by sciurids and Ruffed Grouse (Bonasa umbellus). Productivity calculated from 15 known nesting attempts totaled 32 young for an average of 2.13 young per nesting attempt (range 1-4 young). Goshawks nested in large tracts of mature forests with high levels of canopy cover (82%). The nest site topography was consistent with previous studies finding that goshawks avoid southern slopes. Tree densities in the larger size classes and basal area were characteristic for mature forest. Goshawks constructed their nests in large diameter trees, which averaged 41.7 cm in diameter at breast height. Patch size of contiguous forests surrounding goshawk nests revealed a very high mean of 324.5 ha, thus suggesting that large forest patch size may be important for nesting by this forest interior species. Analysis of 202 ha circles centered on each nest revealed that total forest cover averaged 156.1 ha, which was comprised of 65.2 ha for conifer forest, 75.6 ha for deciduous forest, and 17.4 ha for mixed forest. Overall, the post-fledgling family areas for these nests were dominated by forest cover (>75%). Our results suggest that goshawks usually prefer isolation and little human disturbance at the nest site, but some exceptions were noted. Given the highly fragmented and urbanized landscape of Connecticut, we suggest that goshawk management should focus on providing large tracts of mature forest at least 300 ha in extent.
Keywords: Accipiter; Accipiter gentilis; Aves; Bonasa umbellus; Coniferophyta; Connecticut; Forest; Fragmentation; Habitat; Mammalia; Nest sites; Northern Goshawk; Prey; Productivity; Sciuridae; Site fidelity; dept.bio

Ecology of the Northern Goshawk in the New York-New Jersey Highlands - Bosakowski, T.; Smith, D.G. (Studies in Avian Biology, 2006)
Evidence suggests that the Northern Goshawk (Accipiter gentilis) was once extirpated in the New York-New Jersey Highlands, but has recolonized the Highlands in the 1960s and 1970s following a dramatic reforestation in the 20th century. The reforestation produced large tracts of contiguous mature forest, which appear to be a primary habitat requirement of this species. Most goshawk nests in the Highlands were found deep in remote forest areas where nest sites are typically distant from human habitation and paved roads. Nest trees were almost always built in co-dominant or dominant trees of the stand, but were seldom built in the largest tree of the nesting stand. Canopy cover is very high (90%) and shrub cover is often reduced or nearly devoid (28.3%) at goshawk nest sites. Ruffed Grouse (Bonasa umbellus) appears to be the most common prey, but other predominant bird species in diets of Highlands goshawks included the Blue Jay (Cyanocitta cristata), Mourning Dove (Zenaida macroura), Rock Dove (Columba livia), and blackbirds. Sciurids, including eastern chipmunks (Tamias striatus), red squirrel (Tamiasciurus hudsonicus), and gray squirrel (Sciurus carolinensis) were also important components of goshawk diets from the Northeast. Highlands goshawks had a mean prey weight of 365.8 g, with bird prey averaging 332.3 g and mammal prey averaging 442.9 g. In the Highlands, productivity calculated from 36 nesting attempts averaged 1.4 young per nest, lower than found in two Connecticut studies (1.75 and 2.13). Although the goshawk is generally considered to be a permanent resident, dozens of northeastern hawk migration observation stations reveal a small, but distinct, fall migration during non-invasion years. Breeding bird atlas data confirm that the goshawk is rare in New Jersey, moderately rare in Pennsylvania (mostly northern), and numerous in New York. Various factors impacting Highlands goshawks are discussed including interspecific competition, lack of reserves, timber harvesting, tree diseases, and human disturbance factors.
Keywords: Accipiter gentilis; Aves; Bonasa umbellus; Columba livia; Competition; Cyanocitta cristata; Food-niche overlap; Forestry; Habitat; Mammalia; Migration; Nest sites; New Jersey; New York; Northern Goshawk; Prey; Productivity; Sciuridae; Sciurus carolinensis; Site fidelity; Tamias striatus; Tamiasciurus hudsonicus; Zenaida macroura; dept.bio

Estrogen dependent growth inhibitory effects of tamoxifen but not genistein in solid tumors derived from estrogen receptor positive (ER+) primary breast carcinoma MCF7: single agent and novel combined treatment approaches. - Nobert, Gayle S; Kraak, Martha M; Crawford, Sarah (Bulletin du cancer, 2006)
While many studies have documented tamoxifen's benefits as an adjuvant therapy in the treatment and prevention of recurrent breast cancer in estrogen receptor positive (ER+) breast carcinoma, this beneficial effect may decrease with long-term tamoxifen use. This experimental study was designed to compare the cytotoxic responses of ER+ primary breast cancer solid tumors derived from the MCF7 cell line to experimental therapeutics, including genistein, tamoxifen, all-trans retinoic acid (ATRA) and parthenolide in the presence and absence of exogenous beta-estradiol. The results of this study suggest that the growth inhibitory effects of tamoxifen, were dependent on beta-estradiol levels. In contrast, the cytotoxic effects of the isoflavone soy derivative, genistein, were observed to be independent of exogenous estrogen. Moreover, combined therapy using tamoxifen and genistein produced enhanced cytotoxic effects also independent of beta-estradiol levels. Additional studies involving the use of the novel agents all trans retinoic acid (ATRA) and parthenolide produced notable tumor responses and combined effects that were also estrogen-independent. Overall, these preclinical research findings suggest possible clinical applications suggesting that genistein might be a useful clinical adjuvant, particularly in post-menopausal women in whom breast cancer occurs more frequently. Moreover, this research suggests that combined treatment approaches involving the use of tamoxifen in conjunction with agents that inhibit NFkappaB pathway signaling, such as parthenolide and genistein, warrant further study.
Keywords: *Antineoplastic Combined Chemotherapy Protocols/tu [Therapeutic Use]; *Breast Neoplasms/dt [Drug Therapy]; *Genistein/tu [Therapeutic Use]; *Neoplasms, Hormone-Dependent/dt [Drug Therapy]; *Tamoxifen/tu [Therapeutic Use]; Anticarcinogenic Agents; Anticarcinogenic Agents/tu [Therapeutic Use]; Antineoplastic Agents, Hormonal; Antineoplastic Agents, Hormonal/tu [Therapeutic Use]; Antineoplastic Combined Chemotherapy Protocols; Breast Neoplasms; Breast Neoplasms/ch [Chemistry]; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Resistance, Neoplasm; Drug Resistance, Neoplasm/de [Drug Effects]; Estradiol; Estradiol/pd [Pharmacology]; Female; Genistein; Humans; Neoplasms, Hormone-Dependent; Neoplasms, Hormone-Dependent/ch [Chemistry]; Receptors, Estrogen; Sesquiterpenes; Sesquiterpenes/tu [Therapeutic Use]; Spheroids, Cellular; Spheroids, Cellular/de [Drug Effects]; Tamoxifen; Tretinoin; Tretinoin/tu [Therapeutic Use]; antineoplastic agent; antineoplastic hormone agonists and antagonists; article; breast tumor; chemistry; dept.bio; dose response; drug effect; drug resistance; estradiol; estrogen receptor; female; genistein; human; multicellular spheroid; neoplasm; parthenolide; retinoic acid; sesquiterpene; tamoxifen; tumor cell line; ⛔ No DOI found

The mayflies (ephemeroptera) of new hampshire: seasonality and diversity of the stream fauna - Chandler, Donald S; Whitmore, Greg D; Burian, Steven K; Burger, John F (Transactions of The American Entomological Society, 2006)
Season-long sampling in streams and rivers produced 112 species of mayflies, which with other records totals 121 species for New Hampshire; 88 of these are new state records. Appearance of blackwing/mature larvae were used to develop statements on seasonality of species. Distinct differences were found between the faunas of southern and north-central New Hampshire, with an important factor being water temperatures through the season. A biogeographic analysis coupled with known habitat preferences reinforced the hypothesis that water temperature was a critical factor in determining species distributions in the state.
Keywords: Ephemeroptera; dept.bio

Development of synapses and expression of a voltage-gated potassium channel in chick embryonic auditory nuclei. - Feng, Jane J; Morest, D Kent (Hearing research, 2006)
The potassium channel protein, Kv3.1, is abundantly expressed in the chick auditory pathway. Its b-isoform is found in nucleus magnocellularis, which receives the cochlear input, both before and after the establishment of synaptic connections. It is also present in cell cultures in the absence of any peripheral input. However, the expression of this isoform in the embryo has been shown to increase with development. Here, we address the question of the correlation between maturation of synapses in the auditory pathway and the pattern of expression of the b-isoform in a series of embryos prepared for immunohistochemistry at Hamburger-Hamilton stages equivalent to E10, E12, E14, and E17. We show here that this subunit translocates from the perinuclear cytoplasm to the cell membrane domain in nucleus magnocellularis at the time that cochlear nerve endings emerge as endbulbs of Held (E17). In nucleus laminaris, by this time, while abundant Kv3.1b occurs in the perinuclear cytoplasm, a translocation to the cell membrane domain has not yet occurred, and the mature peri-synaptic localization is delayed to a later stage. This difference suggests a hierarchy in the developmental expression of Kv3.1. An unexpected finding is the expression of the a-isoform of Kv3.1 in astrocytes, especially those which surround the developing nuclei and their connecting fibers. We also report here for the first time the presence of Kv3.1b in the initial segments of axons at the times when they begin to form. Our observations suggest that the Kv3.1 channel protein is regulated through mechanisms linked to the development of synaptic activity.
Keywords: *Cochlear Nucleus/me [Metabolism]; *Olivary Nucleus/ph [Physiology]; *Shaw Potassium Channels/ph [Physiology]; *Synapses/ph [Physiology]; Animals; Astrocyte; Astrocytes; Astrocytes/me [Metabolism]; Astrocytes/ph [Physiology]; Axon initial segment; Chick Embryo; Cochlear Nerve; Cochlear Nerve/em [Embryology]; Cochlear Nerve/me [Metabolism]; Cochlear Nucleus; Cochlear Nucleus/em [Embryology]; Gene Expression Regulation, Developmental; Immunohistochemistry; Kv3.1; Neurons; Neurons/me [Metabolism]; Nucleus laminaris; Nucleus magnocellularis; Olivary Nucleus; Olivary Nucleus/em [Embryology]; Shaw Potassium Channels; Shaw Potassium Channels/me [Metabolism]; Synapses; Translocation; animal tissue; article; astrocyte; auditory nervous system; cell membrane; cellular distribution; chick embryo; chronology; cochlear nerve; controlled study; correlation analysis; cytoplasm; dept.bio; developmental stage; embryo; embryo development; immunohistochemistry; intracellular transport; isoprotein; magnocellular nucleus; maturation; nerve ending; nerve fiber; nervous system development; nonhuman; priority journal; protein content; protein determination; protein domain; protein localization; protein subunit; protein transport; regulatory mechanism; synapse; synaptogenesis; thalamus intralaminar nucleus; voltage gated potassium channel